Hereditary prostate cancer - Wysocka, Barbara; Jassem, Jacek (Contemporary Oncology/Współczesna Onkologia, 2003)
Hereditary prostate cancer, a disorder with strong evidence of genetic heterogeneity, comprises 5% to 10% cases of the disease. As molecular diagnosis is not possible, hereditary prostate cancer is diagnosed based on the pedigree criteria. When three or more individuals are affected in the family and the onset occurs at a young age, the risk of prostate cancer increases up to 35–45%. Autosomal dominant mode of inheritance is most frequent, but there is also evidence on autosomal recessive and X-linked inheritance. Six chromosomal loci with putative prostate cancer susceptibility genes have been mapped: HPC1 (1q24-25), PcaP (1q42-43), HPCX (Xq27-28), CAPB (1p36), HPC2 (17p12), HPC20 (20q13). In addition, two genes, HPC2/ELAC2 (17p12) and RNASEL (1p24-25), have been cloned and are believed to be responsible for hereditary prostate cancer in their mutated variants. Unfortunately, at present presymptomatic genetic testing for mutations in prostate susceptibility genes is not possible. The most prominent clinical feature of hereditary prostate cancer is the age at onset (earlier by 6–7 years) as compared to a sporadic form of the disease. Other clinical features such as the stage, histological Gleason grade, and treatment outcomes do not differ significantly between both forms of prostate cancer. The management of hereditary prostate cancer requires appropriate genetic counseling and presymptomatic screening. Annual serum PSA testing and digital rectal examination are recommended. When PSA exceeds 3 ng/ml, the biopsy of the prostate is required.